A review of the drivers and ecological impacts of estuarine hypoxia - Chen Yiqi; Niu Qianru; Wang Linlin (E3S Web of Conferences)
This review focuses on estuarine hypoxia. Dissolved oxygen is critical to aquatic ecosystems. Estuarine hypoxia can have ecological impacts due to natural and anthropogenic factors. Temperature affects water column stratification and oxygen solubility, exacerbating the risk of hypoxia, and climate change affects marine hypoxia. In addition, nutrients, chlorophyll a and organic matter also play a key role. Estuarine hypoxia is caused by a variety of factors, and understanding its mechanisms is critical to maintaining ecosystem health.